EFFECT OF NETILMICIN ON THE AUDITORY ANALYZER (EXPERIMENTAL STUDY) - I.N. D'yakonova; Yu.S. Ishanova; I.V. Rakhmanova; Ya.M. Sapozhnikov; A.M. Tikhomirov; E.G. Sergeeva (Union of pediatricians of Russia, 2011)
The aim of this work was to study the effect of netilmicin on the auditory analyzer of immature animals (rabbits). This paper presents the results of a survey of 20 intact animals and 24 control animals of the experimental group who received netilmicin in a therapeutic dosage equal to 5 mg/kg per day for 7 days starting from the 12th day of life. Auditory function was assessed according to the registration of short stem-evoked potentials (SSEP) and otoacoustic emission distortion product (OEDP). As a result of therapeutic doses of netilmicin the ototoxic effect has been reveales, which manifests itself in raising the registration threshold of the first peak amplitude of the SSEP and lower average OEDP mainly by reducing the amplitude at frequencies of 4 and 6 kHz. At the same time the experimental group showed a reduction in body weight during the observation period. Key words: immature animals (rabbit), netilmicin, auditory analyzer, the hair cells, Short-stem evoked potentials, otoacoustic emission distortion product. (Pediatric Pharmacology. - 2011; 8 (5): 70-75.)